La ciudadanía laboral y la ciudadanía ambiental como camino hacia la transición justa. Algunas claves desde la participación sindical en temáticas de salud y ambiente en Argentina - Jorge Rubén Afarian (INTER DISCIPLINA, 2026)
In this article, I will provide elements that will contribute to expanding the concept of “labour citizenship” by complementing it with that of “environmental citizenship.” This process is defined through union representation in health and environmental issues, both for and by workers, while also being of interest to and impacting the entire community. In other words, expanding the concept of labor citizenship implies a new level of social and political intervention by workers, specifically through their union associations. The case of the conflict over asbestos contamination in the subway system of the Autonomous City of Buenos Aires, led by the Subway and Premetro Workers’ Union Association (AGTSyP), will serve as a key example of this complementarity. In addition to theories on citizenship, I will draw on the concepts of “collective interest” and “Latin American social medicine–collective health.” Finally, after presenting the case study and the workers’ interventions, I will complete this analysis with the concept of a “just transition”, developed by national and international scholars and promoted by the International Labour Organization. Thus, I aim to establish links between the concepts of labour and environmental citizenship, based on the active participation of workers in disseminating information within their work collective and especially to society at large. The goal is to highlight workers’ experiences in environmental protection. This body of knowledge will be useful in rethinking theoretical categorizations of the world of work (collective interest) and the positioning of union struggles in dialogue with global just transition agendas.